Developing sustainable business models: local knowledge acquisition and tourism lifestyle entrepreneurship - Dias, Á.; Silva, G. M.; Patuleia, M.; González-Rodríguez, M. R. (Journal of Sustainable Tourism, 2023)
Tourism lifestyle entrepreneurs’ (TLEs) businesses are associated with sustainable business models (SBMs) due to a link to the place. This link is a source of essential local knowledge that provides differentiation, competitiveness, and sustainability. Given the importance of local knowledge to SBMs, this article explores knowledge management by examining how TLEs acquire and integrate knowledge as well as its effects on innovativeness and self-efficacy. We use a sequential mixed-methods approach in which we first conducted a qualitative study with four in-depth semi-structured interviews with TLEs, followed by a quantitative study through a survey of 115 TLEs, and third we conducted another qualitative study based on four semi-structured interviews. The results indicate that entrepreneurial communication has a significantly positive and direct effect on both the innovativeness and self-efficacy of TLEs. A community-centered strategy has a positive influence on innovativeness and self-efficacy but via the indirect effect of entrepreneurial communication. Local knowledge assimilation plays a mediating role between the acquisition of local knowledge and innovativeness and self-efficacy. These findings provide a general understanding and framework about how TLEs link the elements of an SBM to greater innovativeness and self-efficacy.